Responsiveness and clinically meaningful improvement, according to disability level, of five walking measures after rehabilitation in multiple sclerosis: a European multicenter study - Baert, Ilse; Freeman, Jennifer; Smedal, Tori; Dalgas, Ulrik; Romberg, Anders; Kalron, Alon; Conyers, Helen; Elorriaga, Iratxe; Gebara, Benoit; Gumse, Johanna; Heric, Adnan; Jensen, Ellen; et al. (Neurorehabilitation and neural repair, 2014)
BACKGROUND: Evaluation of treatment effects on walking requires appropriate and responsive outcome measures. OBJECTIVES: To determine responsiveness of 5 walking measures and provide reference values for clinically meaningful improvements, according to disability level, in persons with multiple sclerosis (pwMS). METHODS: Walking tests were measured pre- and postrehabilitation in 290 pwMS from 17 European centers. Combined anchor- and distribution-based methods determined responsiveness of objective short and long walking capacity tests (Timed 25-Foot Walk [T25FW] and 2- and 6-Minute Walk Tests [2MWT and 6MWT] and of the patient-reported Multiple Sclerosis Walking Scale-12 [MSWS-12]). A global rating of change scale, from patients' and therapists' perspective, was used as external criteria to determine the area under the receiver operating characteristic curve (AUC), minimally important change (MIC), and smallest real change (SRC). Patients were stratified into disability subgroups (Expanded Disability Status Scale score ≤4 [n = 98], >4 [n = 186]). RESULTS: MSWS-12, 2MWT, and 6MWT were more responsive (AUC 0.64-0.73) than T25FW (0.50-0.63), especially in moderate to severely disabled pwMS. Clinically meaningful changes (MICs) from patient and therapist perspective were -10.4 and -11.4 for MSWS-12 (P < .01), 9.6 m and 6.8 m for 2MWT (P < .05), and 21.6 m (P < .05) and 9.1 m (P = .3) for 6MWT. In subgroups, MIC was significant from patient perspective for 2MWT (10.8 m) and from therapist perspective for MSWS-12 (-10.7) in mildly disabled pwMS. In moderate to severely disabled pwMS, MIC was significant for MSWS-12 (-14.1 and -11.9). CONCLUSIONS: Long walking tests and patient-reported MSWS-12 were more appropriate than short walking tests in detecting clinically meaningful improvement after physical rehabilitation, particularly the MSWS-12 for moderate to severely disabled pwMS.
Keywords: dospělí; Reference Standards; Europe; techniky fyzikální terapie; Adult; výsledek terapie; Disability Evaluation; multiple sclerosis rehabilitation; clinically meaningful improvement; lidé; Multiple Sclerosis; responsiveness; Evropa; Physical Therapy Modalities; Recovery of Function; roztroušená skleróza; Treatment Outcome; obnova funkce; referenční standardy; Male; Walking; posuzování pracovní neschopnosti; lidé středního věku; walking measures; mužské pohlaví; Middle Aged; chůze; Humans